2021
DOI: 10.1021/acsami.1c02038
|View full text |Cite
|
Sign up to set email alerts
|

Cerium-Based Metal–Organic Framework Nanocrystals Interconnected by Carbon Nanotubes for Boosting Electrochemical Capacitor Performance

Abstract: In this study, nanocrystals of a cerium-based metal–organic framework (Ce-MOF), Ce-MOF-808, are directly grown on the surface of carboxylic acid-functionalized carbon nanotubes (CNTs) by a facile one-step solvothermal synthesis method. Ce-MOF–CNT nanocomposites with various Ce-MOF-to-CNT ratios are synthesized, and their crystallinity, morphology, porosity, and electrical conductivity are examined. The redox-hopping and electrochemical behaviors of the pristine Ce-MOF in aqueous electrolytes are investigated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 69 publications
7
68
0
Order By: Relevance
“…It is also in line with very recent studies on Ce(IV)-MOF-808. 46 Cerium is well established in various electrochemical processes, 47 but studies of electrochemical applications of MOF have been mostly concentrated on batteries and supercapacitors or water-splitting reactions. 48 Given the affinity of cerium ions to nitrate ions, 47 it would be interesting to explore CTH-15 or related systems in catalytic electrochemical nitrate reduction, an important issue due to a pressing need to remove nitrate from drinking water.…”
Section: Electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…It is also in line with very recent studies on Ce(IV)-MOF-808. 46 Cerium is well established in various electrochemical processes, 47 but studies of electrochemical applications of MOF have been mostly concentrated on batteries and supercapacitors or water-splitting reactions. 48 Given the affinity of cerium ions to nitrate ions, 47 it would be interesting to explore CTH-15 or related systems in catalytic electrochemical nitrate reduction, an important issue due to a pressing need to remove nitrate from drinking water.…”
Section: Electrochemistrymentioning
confidence: 99%
“…59 We see here an opportunity for new families of MOFs: for example, one candidate metal ion being Ce(IV), which we have shown here to be substantially stabilized compared with its aqueous solution chemistry. Ce(IV) MOFs are previously known, 46,[60][61][62][63][64][65][66][67][68][69][70][71][72] but it is not a large class of MOFs, possibly because of the use of Ce(IV) as a well-known oxidant in organic synthesis. However, Ce(IV) may be more stable than we think, 43,44 Figure 6.…”
Section: Rod-and Sheet-mof Synthesismentioning
confidence: 99%
“…Shen et al directly grew Ce-MOF-808 nanocrystals on the surface of carboxylic acid-functionalized CNT. [286] Areal capacitance of the optimal Ce-MOF-808-20CNT electrode was evaluated as 22.4 mF cm À 2 in 0.1 m Na 2 SO 4 electrolyte, which is better than that of Ce-MOF-808. Zheng et al developed congenerous-exfoliation method to prepare Ni 2 + /Ce-MOF with a specific capacitance of 358 F g À 1 at 1 A g À 1 .…”
Section: Re/mof Compositesmentioning
confidence: 96%
“…Shen et al. directly grew Ce‐MOF‐808 nanocrystals on the surface of carboxylic acid‐functionalized CNT [286] . Areal capacitance of the optimal Ce‐MOF‐808‐20CNT electrode was evaluated as 22.4 mF cm −2 in 0.1 m Na 2 SO 4 electrolyte, which is better than that of Ce‐MOF‐808.…”
Section: Re Compounds and Nanocomposites For Scs Applicationmentioning
confidence: 99%
“…1 In addition, our previous study also found that there are on average 3.33 formate ligands coordinated on each node presented in Ce-MOF-808. 2 To investigate the amounts of coordinated formate within these MOFs under the proton-conducting conditions, the MOF solid was exposed to humid air (99% RH) for 24 h, and the resulting sample after activation was digested in a NaOD solution for NMR measurements. As shown in Figure S4, the ratios of the integrated peak area for coordinated formate to that for the three protons of H3BTC in the Ce-MOF-808 and Zr-MOF-808 samples are 0.30 and 0.50, respectively.…”
Section: S2 Additional Characterization Datamentioning
confidence: 99%